On Hegel - Boer, Karin de. author. aut Link
XI, 266 p.
Keywords: Focusing on the Science of Logic , this wide-ranging and innovative reading exposes the force as well as the limit of Hegel's philosophy. Drawing on Hegel's early account of tragic conflicts, De Boer brings into play a form of negativity that challenges the optimism inherent in modernity and Hegelian dialectics alike.